Optimization of solid-state fermentation conditions of rapeseed meal using response surface analysis combined with principal component analysis - WU Yi-fei; YAO Xiao-hong; SUN Hong; WANG Xin; TANG Jiang-wu (浙江大学学报. 农业与生命科学版)
A principal component vector F1 was obtained by principal component analysis for three quality evaluation indexes including glucosinolate degradation rate, crude protein content and peptide recovery ratio in rapeseed meal fermentation, then based on the response surface analysis of F1, the technological parameters were optimized in the solid-state fermentation process of rapeseed meal by Bacillus subtilis BS-012. The results showed that the optimal condition for solid-state fermentation of rapeseed meal was as follows: inoculum size 4.2%, fermentation temperature 30.1 ℃, moisture content 49.9%, and fermentation time 47.3 h. Under the optimal condition, the glucosinolate degradation rate, crude protein content and peptide recovery rate of rapeseed meal were 60.89%, 40.63% and 15.91%, respectively. The results were not significantly different from those under the conditions optimized only using response surface method. In conclusion, the application of principal component analysis combined with response surface method was effective in the optimization of solid-fermentation of rapeseed meal.